TUGAS DAN FUNGSI LURAH DALAM PELAYANAN PUBLIK DI KELURAHAN WERI, KECAMATAN LARANTUKA, KABUPATEN FLORES TIMUR - Belaga, Nurul Alfiah; Ratu Udju, Hernimus; Ermalinda, Jenny (Petitum Law Journal, 2025)
This research was conducted in Weri Village, Larantuka District, East Flores Regency in July 2024 until completion. The formulation of the problem is: To what extent are the duties and functions of the Lurah in public services in Weri Village, Larantuka District, East Flores Regency and What are the factors that influence the duties and functions of the Lurah in public services in Weri Village, Larantuka District, East Flores Regency. The benefits of this research are to contribute to the development of science, especially in the field of Constitutional Law and input for the Weri Village government in carrying out public services. This research uses an empirical legal research method. The data collection techniques used are: Observation, Interviews and Literature Studies in the form of books, laws and regulations, journals and other written materials related to the research topic. The data analysis technique is that all information processed is analyzed using empirical legal methods according to the data obtained by paying attention to the theory, principles and legal rules related to the duties and functions of the Lurah in public services. Suggestions in this writing: The East Flores Regency Government needs to pay attention to the Weri Village organization and the community is expected to be more active in providing feedback regarding services in Weri Village.